Decentralisation in Africa: A Pathway out of Poverty and Conflict? - Christof Hartmann; Gordon Crawford (Amsterdam University Press, 2008)
Grounded in empirically-based country case studies, this new study provides a sober assessment of what decentralisation can achieve. The current momentum for decentralisation of government in Africa and elsewhere in the developing world is unparalleled, but are the benefits claimed by its advocates being realised? Focusing on two claims in particular, this book questions whether decentralisation does offer a significant pathway out of poverty and conflict in Africa. Issues of poverty reduction are addressed in Uganda, Ghana, Malawi and Tanzania, while those of conflict management are explored in Mauritius, Namibia, South Africa, Uganda and Rwanda.
Keywords: 320; Public administration; Economics; Political science